1999
DOI: 10.1002/(sici)1099-1492(199906)12:4<175::aid-nbm552>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Localizedin vivo1H NMR spectroscopy of murine tumours: effect of blood flow reduction

Abstract: Single voxel 1H localized spectroscopy (PRESS at 300 MHz) was used to monitor physiological and biochemical changes induced by hydralazine (5 mg/kg, i.p.) in murine C3H mammary tumours. In addition to a significant increase (by 52%, maximal at 30 min) in the intensity of the 1.32 ppm signal (predominantly from lactate, consistent with a selective reduction in tumour blood supply by hydralazine), downfield shifts in the resonance frequencies of 1H signals were observed. In particular, the signal initially at 3.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Both of the agents are commonly used in clinics. They have also been extensively investigated to modulate blood flow in animal experiments (22,26). …”
Section: Discussionmentioning
confidence: 99%
“…Both of the agents are commonly used in clinics. They have also been extensively investigated to modulate blood flow in animal experiments (22,26). …”
Section: Discussionmentioning
confidence: 99%
“…These factors can be semi-quantitated and followed serially allowing the effects of therapeutic manipulations to be monitored. The technique has been used extensively in animal models looking at the effects of blood flow modifiers such as nicotinamide and carbogen (Robinson et al, 2000), hydralazine (Nielsen et al, 1999) and vascular occlusion (McCoy et al, 1995). One of the major problems of MRS is lack of sensitivity especially in deep-seated human tumours.…”
Section: Magnetic Resonance Spectroscopy (Mrs)mentioning
confidence: 99%
“…Multiple signaling pathways and oncogenes can regulate glycolysis 54. Decreasing tumor oxygenation correlated with increasing glycolytic rate in a murine mammary carcinoma model in a study using volume localized 13 C MRS with 1 H- 13 C cross polarization to detect the conversion of [1- 13 C]-glucose to [3- 13 C]-lactate 63. Several studies showed that [1- 13 C]-labeled glucose is metabolized to lactate in poorly differentiated tumors 6467.…”
Section: Metabolic Molecular and Functional Mrs Of Cancer Cells mentioning
confidence: 99%